2011
DOI: 10.1161/circulationaha.111.037572
|View full text |Cite
|
Sign up to set email alerts
|

Transcoronary Concentration Gradients of Circulating MicroRNAs

Abstract: Background-Circulating levels of microRNA (miR) have been proposed as biomarkers for cardiovascular disease. To identify the heart as a potential source for miRs released into the circulation, we measured concentration gradients across the coronary circulation for muscle-enriched (miR-133a, miR-499, miR-208a), vascular (miR-126, miR-92a), leukocyterelated (miR-155), and platelet-enriched (miR-223) miRs. Methods and Results-Circulating miRs were measured by TaqMan polymerase chain reaction in EDTA-plasma simult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
183
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 254 publications
(192 citation statements)
references
References 31 publications
7
183
1
1
Order By: Relevance
“…This concept is in line with a study from da Rosa et al, who showed that circulating miR-126 is consumed most probably from the endothelium during the passage of the culprit lesion in patients with an acute coronary syndrome. 32 Considering that miR-126 is highly expressed and mainly transported within EMPs, 15 these findings support the concept that the ischemic endothelium increases its abilities to take up EMPs to prevent cell damage and death.…”
Section: Discussionmentioning
confidence: 63%
“…This concept is in line with a study from da Rosa et al, who showed that circulating miR-126 is consumed most probably from the endothelium during the passage of the culprit lesion in patients with an acute coronary syndrome. 32 Considering that miR-126 is highly expressed and mainly transported within EMPs, 15 these findings support the concept that the ischemic endothelium increases its abilities to take up EMPs to prevent cell damage and death.…”
Section: Discussionmentioning
confidence: 63%
“…miRNAs are ideal biomarkers since they are stable and their sequences can be easily amplified. Alterations in circulating miRNA profiles have been associated with cardiovascular risk factors such as hypertension, diabetes, and dyslipidemias as well as with cardiovascular diseases such as coronary heart disease, myocardial infarction, and heart failure de Rosa et al 2011). However, this association has not been found in all studies (Wagner et al 2013).…”
Section: Hdl Functionmentioning
confidence: 99%
“…The miR-126 levels in the plasma have been positively and negatively associated with various cardiovascular clinical entities. [13][14][15] Even though the reported studies did not distinguish between miR-126 in protein complexes and vesicles, it was found that circulating miR-126 decreases during transcoronary passage, 16 which could indicate an uptake of miR-126 by, for example, smooth muscle cells, thereby aggravating atherosclerosis. However, whether protein-bound miR-126 is also released into the circulation or whether it is just secreted to the basal side of endothelial cells into the intima is not known but highly likely, because miR-126 is found in protein complexes and vesicles in plasma.…”
mentioning
confidence: 98%